An Evaluative Study of a Health Information Management Program Following a Significant Curriculum Change--Part 1. - Peterson, Jennifer (Perspectives in Health Information Management)
The advent of electronic health records has led to significant changes in the role of health information management (HIM) professionals. These changes have required significant changes in the educational training required for HIM professionals, leading to new curriculum requirements. To meet the need for well-prepared professionals in the changing HIM environment, it is essential for educational programs to ensure that they are effectively preparing students for the new roles they will be expected to fill. This indepth case study of one HIM academic program contributes to a program review and evaluation to determine the impact of the recent required curriculum changes on the program. This study used a utilization-focused evaluation framework that included evaluation capacity building. The study specifically assessed the ability of the recent curriculum changes to adequately prepare students for the current HIM field as well as the effects of the changes on the program as a whole. This evaluative study goes beyond the use of metrics such as enrollment, retention, and RHIA exam pass rates and delves deeper through surveys, interviews, and focus groups to collect data on the students', graduates', and employers' perceptions. Through the study, major themes were identified, including perceptions of student satisfaction and student preparedness, perceptions of the new curriculum, concern about loss of parts of the old curriculum, and future needs for the HIM program and for the HIM field in general. While many findings were expected, some surprising or unexpected findings included concern about loss of parts of the old curriculum, and close alignment between respondents' area of interest or career path and perceptions of the new versus old curriculum. The study allowed the program to assess preparation of students for the current HIM field as well as other effects of the curriculum changes on the program. This assessment allowed for a true evaluation of the modified curriculum as well as identification of areas for improvement.